Analisis Etika Bisnis dan Penyalahgunaan Wewenang dalam Kasus Investasi - Ali Rahman Fauji; Halimah Zahrah; Aulia Rahadatulaisyi; Feisal Rahman Setiawan; Mutia Damayanti (PENG: Jurnal Ekonomi dan Manajemen, 2025)
The application of ethical business law is becoming increasingly important in today's complex corporate world, especially in the context of ethical violations that can harm various parties, including consumers, employees, and other stakeholders, as highlighted by the case of PT Jouska Financial Indonesia involving unauthorized management of client funds and manipulation of funds that caused financial losses and a crisis of public confidence. This research aims to deeply analyze the violation of business ethics principles by PT Jouska and examine its empirical impact on public trust and regulation of the financial services industry in Indonesia. Using a qualitative method with a case study approach, this research analyzes PT Jouska Financial Indonesia as the unit of analysis through document study and literature review, with descriptive and interpretive data analysis techniques. The results show that PT Jouska has violated the principles of honesty and integrity by managing client funds in a non-transparent manner, conducting adverse transactions without consent, and manipulating financial statements, resulting in financial losses, loss of trust, and a negative impact on the company's reputation and regulatory oversight. Therefore, it is recommended that the implementation of strong legal business ethics should be prioritized to prevent similar violations, protect consumer rights, and safeguard the company's reputation, through policy reforms, strengthening of supervisors, and strengthening of regulatory oversight.